Planning for Online Education: A Systems Model - Picciano, Anthony G (Online Learning, 2015)
The purpose of this article is to revisit the basic principles of technology planning as applied to online education initiatives. While not meant to be an exhaustive treatment of the topic, the article is timely because many colleges and universities are considering the development and expansion of online education as part of their planning activities. The article suggests that purposeful planning is key to the successful implementation of online education as opposed to disruption or radical transformation that may be damaging to an institution’s culture.